Analisis Penerapan Supply Chain Management Pada Produk Dodol Pasar Bengkel Diperbaungan Serdang Bedagai - Lubis, Suci Arifah; Mahfadillah, Aninda; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Supply Chain Management (SCM) or supply chain is a concept that discusses marketing, as well as sustainable costs that aim to help the business development process. One of the businesses managed at the workshop market in Perbaungan Serdang Bedagai is lunkhead products. Currently, lunkhead products are the best sellers in the workshop market. This study aims to see how the implementation of the supply chain used in the dodol business. The data collection method used is the method of collecting data from various sources on the internet, by connecting these sources into one. This is done by studying book references, articles, and browsing the internet, as well as literature reviews related to system analysis and surveys.